First evidence of Archean mafic dykes at 2.62 Ga in the Yilgarn Craton, Western Australia: Links to cratonisation and the Zimbabwe Craton - Stark, J. Camilla; Wilde, Simon; Söderlund, U.; Li, Zheng-Xiang; Rasmussen, Birger; Zi, Jianwei (Elsevier BV, 2018)
© 2018 Elsevier B.V. The Archean Yilgarn Craton in Western Australia hosts at least five generations of Proterozoic mafic dykes, the oldest previously identified dykes belonging to the ca. 2408–2401 Ma Widgiemooltha Supersuite. We report here the first known Archean mafic dyke dated at 2615 ± 6 Ma by the ID-TIMS U-Pb method on baddeleyite and at 2610 ± 25 Ma using in situ SHRIMP U-Pb dating of baddeleyite. Aeromagnetic data suggest that the dyke is part of a series of NE-trending intrusions that potentially extend hundreds of kilometres in the southwestern part of the craton, here named the Yandinilling dyke swarm. Mafic magmatism at 2615 Ma was possibly related to delamination of the lower crust during the final stages of assembly and cratonisation, and was coeval with the formation of late-stage gold deposit at Boddington. Paleogeographic reconstructions suggest that the Yilgarn and Zimbabwe cratons may have been neighbours from ca. 2690 Ma to 2401 Ma and if the Zimbabwe and Kaapvaal cratons amalgamated at 2660–2610 Ma, the 2615 Ma mafic magmatism in the southwestern Yilgarn Craton may be associated with the same tectonic event that produced the ca. 2607–2604 Ma Stockford dykes in the Central Zone of the Limpopo Belt. Paleomagnetic evidence and a similar tectonothermal evolution, including coeval low-pressure high-temperature metamorphism, voluminous magmatism, and emplacement of mafic dykes, support a configuration where the northern part of the Zimbabwe Craton was adjacent to the western margin of the Yilgarn Craton during the Neoarchean. Worldwide, reliably dated mafic dykes of this age have so far been reported from the Yilgarn Craton, the Limpopo Belt and the São Francisco Craton.